2022
DOI: 10.1002/ana.26363
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Therapy for Infantile Spasms: A Call to Action

Abstract: The aim of this study was to determine whether selection of treatment for children with infantile spasms (IS) varies by race/ethnicity. Methods: The prospective US National Infantile Spasms Consortium database includes children with IS treated from 2012 to 2018. We examined the relationship between race/ethnicity and receipt of standard IS therapy (prednisolone, adrenocorticotropic hormone, vigabatrin), adjusting for demographic and clinical variables using logistic regression. Our primary outcome was treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Although the absolute values and costs may change, it is likely that the temporal trends in costs and use would be similar in these populations. Prior literature has identified inequities in the treatment of IESS: non‐Hispanic Black patients and patients with public insurance have a lower likelihood of receiving a standard treatment course with a first‐line treatment as the initial or second treatments 40 . Unfortunately, the MarketScan database does not include data on race or zip code to evaluate whether these inequities have changed over the years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the absolute values and costs may change, it is likely that the temporal trends in costs and use would be similar in these populations. Prior literature has identified inequities in the treatment of IESS: non‐Hispanic Black patients and patients with public insurance have a lower likelihood of receiving a standard treatment course with a first‐line treatment as the initial or second treatments 40 . Unfortunately, the MarketScan database does not include data on race or zip code to evaluate whether these inequities have changed over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has identified inequities in the treatment of IESS: non-Hispanic Black patients and patients with public insurance have a lower likelihood of receiving a standard treatment course with a first-line treatment as the initial or second treatments. 40 Unfortunately, the MarketScan database does not include data on race or zip code to evaluate whether these inequities have changed over the years. Future studies will evaluate whether the trends we found in our population (increase in cost and decrease in use of affect differently patients of different races, socioeconomic statuses, and different insurance types.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…13,[15][16][17][18][19] That racial and ethnic inequities exist for infants highlights how structural racism affects epilepsy care across age groups. 8 Health care disparities borne disproportionately by vulnerable populations, such as BIPOC children with IESS, can be catastrophic. In early onset epilepsy, as little as 1-month treatment delay was associated with an intelligence quotient loss of 12.4 points.…”
Section: Discussionmentioning
confidence: 99%
“…22 Structural racism has been used to describe this complex ecosystem and is a well-recognized social determinant of health, resulting in worse outcomes in pediatrics, neurology, and epilepsy. 8,21,[23][24][25][26] Determining precisely how structural racism impacts children with IESS will require further study and should integrally involve participation of affected families. 12 Despite this being a single-centered study with full access to all records, we were unable to determine precise causes for delays in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation